2002
DOI: 10.1080/15428110208984767
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Commercially Available Fit-Test Methods

Abstract: American National Standards Institute (ANSI) standard Z88.10, Respirator Fit Testing Methods, includes criteria to evaluate new fit-tests. The standard allows generated aerosol, particle counting, or controlled negative pressure quantitative fit-tests to be used as the reference method to determine acceptability of a new test. This study examined (1) comparability of three Occupational Safety and Health Administration-accepted fit-test methods, all of which were validated using generated aerosol as the referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…The ANSI criteria for accepting new fit tests are advisory and recognize that a reference standard for quantitative fit testing does not exist. Janssen et. al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ANSI criteria for accepting new fit tests are advisory and recognize that a reference standard for quantitative fit testing does not exist. Janssen et. al.…”
Section: Discussionmentioning
confidence: 99%
“…Experience in this laboratory has shown that people who participate in fit tests on a frequent basis and who are allowed to perform user seal checks, can adjust most respirators to fit well enough to pass a fit test (Janssen, 2002). For this reason, the subjects were instructed to adjust the facepiece until comfortable but were not permitted to perform a user seal check.…”
Section: Methodsmentioning
confidence: 99%
“…25,26 Generally, several studies regarding the QLFT procedure were performed using commercial nebulizers. 10,[16][17][18]20,[27][28][29] Furthermore, Huang et al explored some medical nebulizers and found those nebulizers could be substituted for the OSHA-approved ones. 30 Notably, some studies were carried out concerning the QLFT protocol using commercial nebulizers in Iran by Jahangiri et al 16,31,32 It seems that all of those studies were aimed to assess the feasibility of some substitutions for the QLFT protocols and introduce the cost-benefit and reliable solutions (options) to all respirator users in order to focus on the importance of conducting fit testing protocols and improving culture and attitude towards the fit testing procedures as one of the most important components of the respiratory protection program (RPP).…”
Section: Introductionmentioning
confidence: 99%
“…In the conventional Portacount fit‐test method, leakage is measured during a sampling period of 30 s; this figure is used to calculate a mean leakage for the period of the entire fit test. An instantaneous leak or relatively high leakage during a single exercise can be offset by longer periods of lower leakage in that single exercise, resulting in an overall passing fit factor in a single exercise . Studies show that health‐care workers are increasingly becoming exposed to, and contracting, Pulmonary tuberculosis (TB) in the workplace, particularly multiple‐drug‐resistant TB…”
Section: Introductionmentioning
confidence: 99%